Optimal Performance of Pole Number Combination in Permanent Magnet Motor - Shamsul Kahar, Muhammad Farid; Aziz, Roziah (Evolution in Electrical and Electronic Engineering, 2024)
Permanent magnet synchronous motors (PMSMs) demonstrate great efficiency, power density, and torque-to-weight ratio in the dynamic sector of electrical machines. On the other hand, the number of rotor poles in a permanent magnet motor significantly affects its performance, including torque, speed, efficiency, and power density. As a result, the purpose of this project is to improve the PMSM's performance by changing the arrangement of pole numbers. In this research, the JMAG programme is used to design the rotor, permanent magnet, stator, and armature coil as a 2D finite element using JMAG Designer. The development and evaluation of three designs with different pole numbers were observed and determined using effective design and coil test analysis, as well as testing for performance under no load and load situations. The operating principles of all three designs have been examined and the operating principle of each design with varied pole numbers was identified.